Changes in the Total Fecal Bacterial Population in Individual Horses Maintained on a Restricted Diet Over 6 Weeks - Dougal, Kirsty; Harris, Patricia A.; Girdwood, Susan E.; Creevey, Christopher J.; Curtis, Gemma C.; Barfoot, Clare F.; Argo, Caroline M.; Newbold, Charles J. (Frontiers in Microbiology, 2017)
Twelve mature (aged 5-16 years) horses and ponies of mixed breed and type were fed restricted (1.25% BM Dry matter) quantities of one of two fibre based diets formulated to be iso-caloric. Diet 1 comprised of 0.8% body mass (BM) of chaff based complete feed plus 0.45% BM low energy grass hay (the same hay used for both diets). Diet 2 comprised 0.1% BM of a nutrient balancer plus 1.15% BM grass hay. Faecal samples were collected at week 10 and week 16. DNA was extracted and the V1-V2 regions of 16SrDNA were 454-pyrosequenced to investigate the bacterial microbiome of the horse. The two most abundant phyla found in both diets and sampling periods were the Firmicutes and Bacteroidetes. There was a clear reduction in Bacteroidetes with a concordant increase in Firmicutes over time. There was a limited degree of stability within the bacterial community of the hindgut of horses, with 65% of bacteria retained, over a 6 week period whilst on a uniform diet. The presence of a core community defined by being present in all samples (each animal/diet combination) included in the study and being present at 0.1% relative abundance (or greater) was identified. In total 65 OTUs were identified that fit the definition of core making up 21-28% of the total sequences recovered. As with total population the most abundant phyla were the Bacteroidetes followed by the Firmicutes, however there was no obvious shift in phyla due to period. Indeed, when the relative abundance of OTUs was examined across diets and periods there was no significant effect of diet or period alone or in combination on the relative abundance of the core OTUs.